Numerical simulation of liquid atomisation - Wan Muhammad Mukhlis, Wan Ab Latif (2010)
The focus of this study was to investigate the spray characteristics and atomization performance of gasoline fuel (G100) and ethanol fuel (E100) in a high pressure chamber. The overall spray and atomization characteristics such as an axial spray tip penetration, spray width, and overall SMD were measured experimentally and predicted by using ANSYS Fluent. The development process and the appearance timing of the vortices in the test fuels were very similar. Moreover, the increased injection pressure induced the occurrence of a clear circular shape in the downstream spray and a uniform mixture between the injected spray droplets and ambient air. The axial spray tip penetrations of the test fuels were similar, while the spray width and spray cone angle of G100 were slightly larger than the other fuels. In terms of atomization performance, the E100 fuel among the tested fuels had the largest droplet size because E100 has a high kinematic viscosity and surface tension.